Antispasmodic Activity of Dried Ginger 70% Methanolic Crude Extract in Isolated Smooth Muscle Preparations - Ghayur, Muhammad Nabeel; Gilani, Anwarul Hassan (Pharmacognosy Communications)
Objectives: Ginger (Zingiber officinale Roscoe) is a popular edible herb consumed and known globally for its culinary and medicinal properties. Particularly in South Asia, the ginger rhizome is used in several Gastrointestinal (GI) related ailments. In this study, we report preliminary findings on the GI relaxant activity of the dried variety of ginger rhizome. Materials and Methods: Ginger rhizome was soaked in 70% aqueous-methanol and dried to give the extract (Gd.Ex). Segments of different isolated smooth muscle preparations were suspended in tissue baths. Results: Phytochemistry profiling showed that the extract has terpenoids, phenols, and alkaloids. On baseline of isolated tissues like rat stomach pylorus, rabbit jejunum, guinea-pig ileum and colon, and rat uterus, Gd.Ex was devoid of any stimulant effect up to 10 mg/mL. The extract was able to completely inhibit spasmogenicity induced with K+ 80 mM in stomach pyloric strips, indicating a Ca2+ Channel Blocking (CCB) mechanism. Gd.Ex in bolus (1-10 mg/mL) and cumulative dosing (0.3-3 mg/mL), showed a relaxant effect on spontaneously contracting baseline of rabbit jejunum. The extract was then tested against different standard GI stimulants like acetylcholine (ACh, 0.3 μM), histamine (0.3 μM), and K+ (50 mM) in guinea-pig ileum. Gd.Ex (3 mg/mL) pretreatment abolished the stimulant responses. A similar inhibitory effect of the extract (0.3-1 mg/mL) was observed in guinea-pig colon and rat uterus against ACh. Conclusion: The study shows the spasmolytic potential of dried ginger extract in different smooth muscle preparations. Together with the earlier published results of dried ginger in rat stomach fundus, this explains the benefit of ginger in potentiating gastric emptying and alleviating nausea.
Keywords: Zingiber officinale; Rhizome; Antidiarrheal; Rat; Rabbit; Guinea-pig